Geothelphusa makatao sp. nov. (Crustacea: Brachyura: Potamidae), a new freshwater crab from an uplifted Pleistocene reef in Taiwan - Shih, Hsi-Te; Shy, Jhy-Yun (Zootaxa, 2009)
A new species of potamid freshwater crab, Geothelphusa makatao, is described from southwestern Taiwan, based on morphological characters and mitochondrial DNA evidence. The new species differs from close congeners, G. pingtung Tan & Liu, 1998, G. shernshan Chen, Cheng & Shy, 2005, and G. ancylophallus Shy, Ng & Yu, 1994 and a superficially similar species, G. albogilva Shy, Ng & Yu, 1994, in the structure of its ambulatory legs, thoracic sternum, male abdomen, and male first pleopods. The unique gene sequences of 16S rRNA and cytochrome oxidase I also support the recognition of this coastal population, which is isolated from other closely related species inhabiting montane areas. Except for G. makatao, the phylogenetic analysis showed that there are three additional hill subclades within the G. pingtung clade, G. shernshan, G. pingtung and the Liangshan subclade, situated in different watersheds of rivers or streams near the Central Range in the southwestern Taiwan.